The Political Geography of Regional Diplomacy in the Russian Federation - Jackson, Thomas (University of Cambridge, 2020)
This thesis investigates the political geography of regional diplomacy in the Russian Federation. The international activities of regions, often referred to as paradiplomacy, has a contested history since the formation of the Russian state in 1991. During a period of decentralised power and regional autonomy claims, paradiplomacy practices burgeoned under the Yeltsin government. However, after two decades of Putin’s centralising reforms much of this regional autonomy, including the right to pursue international activities, has been constrained. Based on qualitative research including interviews with paradiplomatic practitioners across Russia and Europe, textual analysis, and participant observation, this thesis critically analyses the contemporary international activities of Russian regions in this contested environment. Multi-sited fieldwork specifically focuses on three case study regions, each heavily engaged in paradiplomacy, but acting through deeply contrasting international political structures. Comparing the activities of the Republic of Tatarstan, the Republic of Karelia, and St Petersburg highlights the differentiated, and highly spatialised, aspects of paradiplomacy. The thesis analyses paradiplomacy in relation to four core themes: federalism and the region’s relationship with the Russian state; the production of spatialised identity through paradiplomacy; the specific sites of paradiplomacy and their material configurations; and the foreign policy implications of Russian paradiplomacy. Theoretically, the thesis approaches paradiplomacy from a political geography perspective where the primary concern is to illuminate the intersection of space and power in international regional activities. To do so, it draws on practice theory to integrate analysis of the repeated patterns of diplomatic behaviour with their material and discursive context. It is argued that regions should be considered as fully-fledged geopolitical actors capable of reshaping both federal and international relationships. In this ...